PELATIHAN KEWIRAUSAHAAN DAN PENGEMASAN PRODUK UNTUK MENINGKATKAN DAYA SAING KELOMPOK UMKM KELURAHAN SAWUNGGALING SURABAYA - Asandimitra, Nadia; Wardoyo, Dewie Tri Wijayati; Iriani, Sri Setyo; Kistyanto, Anang; Hariyati, Hariyati; Amelia, Ratih (Jurnal Abdi Insani, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national economy, making a significant contribution to economic growth and development. In Indonesia, the presence of MSMEs greatly aids in reducing unemployment caused by limited labor absorption in the formal sector. The number of MSMEs in Indonesia, including in the Sawunggaling sub-district of Surabaya, continues to increase. The Sawunggaling sub-district itself has numerous potentials that can be developed into business activities. Unfortunately, due to limited human resource competencies, the creative spaces available have not been fully utilized by partners. Partners also face difficulties in designing attractive food and beverage packaging. This program aims to optimize existing facilities and provide training to foster entrepreneurial spirit and improve MSME skills in terms of food and beverage packaging design. The activities implemented include enhancing understanding and skills through training that introduces entrepreneurial strategies and product packaging, including incorporating MSME identity into the packaging. The results of the PKM activities show that the PKM target was achieved well, namely an increase in awareness and knowledge among MSME actors in the food and beverage sector in the Sawunggaling sub-district, Surabaya, about the importance of entrepreneurial mindset and product packaging, as well as packaging design ideas that can enhance competitiveness.